Theatre Scene and Theatre Public in Early Modern London. (2nd January 2018) - Doty, Jeffrey S.; Gurnis, Musa
ABSTRACT: Criticism on early modern theatre and the public sphere has primarily examined internal evidence in scripts to show how plays offered contemporary political events and controversies to the critical scrutiny of playgoers. Theatre mediated and transmitted the world of courtly politics to a wider public. However, it also conducted a lateral, popular circulation of the non-elite "private" world (in which the commercial theatre itself was located). This paper investigates the porous performance zones of the "theatre scene", from stories about alehouse patrons making actors do bits from plays to theatre fans incorporating gestures and lines from plays in their daily lives to the creation of an oral history of the early modern theatre through gossip and lore. We explore, then, the "private" consumption of cultural goods as creative, performative acts in their own right; these acts were intelligible within a public that was defined not just by the transmission of political information but also by specific styles of speaking, dressing and relating to others socially – the locus of which was a theatre that constantly recirculated those styles back to its public.